Diabetes Melitus Emergency Prevention Behavior: Hyperglycaemia With Health Belief Model - Arina Ainul Fadlilah; Tri Cahyo Sepdianto; Dewi Rachmawati (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Diabetes melitus emergencies are drastic changes in blood sugar levels that result in a decrease in consciousness if no prevention is taken. The Health Belief Model is a health behaviour theory to understand individual health behaviour including six basic components (Perceived Vulnerability, Perceived Severity, Perceived Benefits, Perceived Barriers, Cues to Action, self-efficacy. This study was conducted to determine the prevention behaviour of diabetes melitus emergencies: hyperglycemia with the Health Belief Model approach. This research uses descriptive method. The sample size was 30 DM patients who were taken with purposive sampling technique. Data collection using a questionnaire of preventive behaviour of diabetes melitus emergencies: belief-based hyperglycaemia as many as 19 questions. Data analysis technique using univariate analysis. A total of 46.7% of DM patients have a vulnerable risk of hyperglycaemia, 40% of DM patients have a severe risk of hyperglycaemia, 50% of DM patients have a beneficial risk of hyperglycaemia, 36.7% of DM patients have a risk of obstacles, 50% of DM patients have a capable risk of hyperglycaemia, 50% of DM patients have a risk of hyperglycaemia encouragement all tend to prevent hyperglycaemia. Diabetes melitus emergency prevention behaviour: hyperglycaemia tends to prevent hyperglycaemia because they are aware of the importance of controlling blood sugar levels, afraid of the dangers of diabetes complications, feel the benefits of treatment and a healthy lifestyle, motivated to behave healthily, supported by counseling and family support, high motivation in preventing hyperglycaemia.